Optimalisasi Kinerja Proteksi Recloser Jaringan Distribusi 20kV Penyulang RDT03 Menggunakan Algoritma Particle Swarm Optimization - Waritza, Heryogka Ahmad; Gunawan, Gunawan; Nugroho, Agus Adhi (Elektrika, 2023)
The reliability of an electric power distribution network system is very important to ensure a good quality of service for consumers. The focus of this study is to find the optimal protection coordination design, topology and operating scheme for RDT03 refiners in the Tambak Aji Industrial Estate. To show the level of reliability and continuity of the electric power distribution network, the SAIFI index (System Average Interruption Frequency Index) and the SAIDI index (System Average Interruption Duration Index) are used. The existing recloser located in section 25 resulted in a SAIFI value of 0.8933 and a SAIDI of 2.407. Using the PSO (Particle Swarm Optimization) optimization method, the results were obtained that the Best Fitness for the most optimal recloser placement was in section 29 with a SAIFI value of 0.32575 and a SAIDI value of 1.0558. This change in recloser placement resulted in a decrease in SAIFI by 36% or by 0.5675 times / year / customer and a decrease in the value of SAIDI by 43.61% or by 1.3649 hours / year / customer. Thus, there is an increase in network reliability if the recloser at the RDT03 feeder is relocated to the location of section 29. Keywords: Reliability, Recloser, SAIFI, SAIDI, Particle Swarm Optimization ABSTRAK Keandalan suatu sistem jaringan distribusi tenaga listrik merupakan hal yang sangat penting untuk menjamin mutu pelayanan yang baik bagi konsumen. Fokus dari penelitian ini adalah untuk mencari desain koordinasi proteksi, topologi dan skema operasi yang optimal untuk penyulang RDT03 di Kawasan Industri Tambak Aji. Untuk menunjukkan tingkat keandalan dan kontinuitas jaringan distribusi tenaga listrik digunakan indeks SAIFI (System Average Interruption Frequency Index) dan indeks SAIDI (System Average Interruption Duration Index). Hasil optimalisasi menggunakan PSO (Particle Swarm Optimization), didapatkan hasil bahwa Best Fitness untuk penempatan recloser yang paling optimal adalah pada section 29 dengan nilai SAIFI sebesar 0.32575 dan nilai SAIDI sebesar 1.0558. Dengan menggunakan PSO, diperoleh lokasi letak recloser yang baru dengan nilai SAIFI yang lebih optimal dengan penurunan sebesar 36% atau sebesar 0,5675 kali/tahun/pelanggan dan penurunan nilai SAIDI sebesar 43,61% atau sebesar 1,3649 jam/tahun/pelanggan. Jika dibandingkan dengan letak recloser exsisting, recloser existing terletak pada section 25 dengan nilai SAIFI sebesar 0,8933 dan SAIDI sebesar 2,407. Dengan demikian terdapat peningkatan keandalan jaringan jika recloser pada penyulang RDT03 direlokasi menuju lokasi section 29.